Social Media Advertising, Conformity, and Environment on Hedonist Lifestyle Through Consumptive Behavior - Nikma Yucha; Rif’atul Nurindah (Journal of Applied Management and Business, 2023)
This study aims to prove and analyze the effect of social media advertising, conformity, and the environment on the hedonic lifestyle of students through their consumptive behavior towards fashion. This study uses quantitative methods, and data collection using questionnaires. The sample was selected using non-probability sampling with a total of 100 respondents. And data processing and analysis using SEM (Structural Equation Modeling). The results of this study can be concluded that social media advertising variables affect fashion consumptive behavior positively and significantly. Conformity affects fashion consumptive behavior positively and significantly. The environment influences fashion consumptive behavior positively and significantly. Fashion consumptive behavior affects the hedonic lifestyle positively and significantly. Social media advertising does not affect the hedonic lifestyle positively and significantly. Conformity is not a hedonic lifestyle in a positive and significant way. The environment influences the hedonic lifestyle positively and significantly. The implications of this research for readers are expected to increase knowledge and can add references in the application of SEM Analysis. And as a basis for follow-up suggestions for business and service activists related to factors that help improve sales.